Association of specific ACE2 and TMPRSS2 variants with circulatory cytokines of COVID-19 Emirati patients - Elemam, Noha M.; Bouzid, Amal; Alsafar, Habiba; Ahmed, Samrein BM; Hafezi, Shirin; Venkatachalam, Thenmozhi; Eldohaji, Leen; Al Hamidi, Tasneem; Gerges, Peter Habib; Halabi, Nour; Hadj-Kacem, Hassen; Talaat, Iman M.; et al. (Frontiers in Immunology, 2024)
The COVID-19 pandemic represented one of the most significant challenges to researchers and healthcare providers. Several factors determine the disease severity, whereas none alone can explain the tremendous variability. The Single nucleotide variants (SNVs) in angiotensin-converting enzyme-2 (ACE2) and transmembrane serine protease type-2 (TMPRSS2) genes affect the virus entry and are considered possible risk factors for COVID-19. We compiled a panel of gene variants from both genes and used in-silico analysis to predict their significance. We performed biological validation to assess their capacity to alter the ACE2 interaction with the virus spike protein. Subsequently, we conducted a retrospective comparative genome analysis on those variants in the Emirati patients with different disease severity (total of 96) along with 69 healthy control subjects.Our results showed that the Emirati population lacks the variants that were previously reported as associated with disease severity, whereas a new variant in ACE2 "Chr X:g.15584534" was associated with disease severity specifically among female patients.In-silico analysis revealed that the new variant can determine the ACE2 gene transcription. Several cytokines (GM-CSF and IL-6) and chemokines (MCP-1/CCL2, IL-8/CXCL8, and IP-10/CXCL10) were markedly increased in COVID-19 patients with a significant correlation with disease severity. The newly reported genetic variant of ACE2 showed a positive correlation with CD40L, IL-1β, IL-2, IL-15, and IL-17A in COVID-19 patients. In conclusion, whereas COVID-19 represents now a past pandemic, our study underscores the importance of genetic factors specific to a population, which can influence both susceptibility to viral infections and the level of severity; subsequently expected required preparedness in different areas of the world.